TSC1 enables plastid development under dark conditions, contributing to rice adaptation to transplantation shock. Issue 2 (12th February 2018) - Shi, Xiaoliang; Chen, Sunlu; Peng, Yu; Wang, Yufeng; Chen, Jiugeng; Hu, Zhanghua; Wang, Baohe; Li, Aihong; Chao, Daiyin; Li, Yuhong; Teng, Sheng
Abstract: Since its domestication from wild rice thousands of years ago, rice has been cultivated largely through transplantation. During transplantation from the nursery to the paddy field, rice seedlings experience transplantation shock which affects their physiology and production. However, the mechanisms underlying transplantation shock and rice adaptation to this shock are largely unknown. Here, we isolated a transplant‐sensitive chloroplast‐deficient ( tsc1 ) rice mutant that produces albino leaves after transplantation. Blocking light from reaching the juvenile leaves and leaf primordia caused chloroplast deficiencies in transplanted tsc1 seedlings. TSC1 encodes a noncanonical adenosine triphosphate‐binding cassette (ABC) transporter homologous to AtNAP14 and is of cyanobacterial origin. We demonstrate that TSC1 controls plastid development in rice under dark conditions, and functions independently of light signaling. However, light rescued the tsc1 mutant phenotype in a spectrum‐independent manner. TSC1 was upregulated following transplantation, and modulated the iron and copper levels, thereby regulating prolamellar body formation during the early P4 stage of leaf development. Therefore, TSC1 is indispensable for plastid development in the absence of light, and contributes to adaptation to transplantation shock. Our study provides insight into the regulation of plastid development and establishes a framework for improving recovery from transplantation shock in rice. Abstract : Rice has been cultivated largely through transplantation. We examined a transplant‐sensitive chloroplast‐deficient mutant, and found that transplantation blocks light from reaching the juvenile leaves and leaf primordia. TSC1, a noncanonical ATP‐binding cassette transporter, controls plastid development under dark conditions. Consequently, TSC1 contributes to rice adaptation to transplantation shock.